(untitled) (Fiep Bulletin - online, 2025)
Introduction: Physical Education professionals are multidisciplinary professionals, including those working in multidisciplinary teams of health care programs. Therefore, their training should include basic subjects that allow them to understand human physiology. Among these, Cellular Biology constitutes the basis of physiology, anatomy and histology, since health ultimately depends on cells. Objective: To analyze, through the Political Pedagogical Projects of Courses (PPPC), the approach to Cellular Biology in Bachelor’s Degree courses in Physical Education of Brazilian public Higher Education Institutions. Results: Through qualitative documentary research, the PPPC analyzed (1) the offer of the subject of cellular biology and/or subjects with content related to cellular biology (total workload), (2) period of the course in which the subject is indicated, (3) nature (mandatory or optional), (4) methodology (practical and/or theoretical and/or extension with respective workload) and (5) content covered. Conclusion: The curricula need to be revised to include the study of cells, since this structure is the basis of the tissues, organs and systems of the human body. This would contribute to a more solid training of physical educators to work in the health area.